Benzobisthiadiazole-based conjugated donor–acceptor polymers for organic thin film transistors: effects of π-conjugated bridges on ambipolar transport1. Issue 6 (14th February 2015) - Wang, Yang; Kadoya, Tomofumi; Wang, Lei; Hayakawa, Teruaki; Tokita, Masatoshi; Mori, Takehiko; Michinobu, Tsuyoshi
<x xml:space="preserve">Abstract</x> Inserting different π-spacers into the polymer backbone allows tailoring of the opto-electrical properties, molecular organizations, and the type of charge carriers in the TFTs.